2014
DOI: 10.1063/1.4872218
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide ion dissociations after inner shell excitation and ionization: The origin of site-specific effects

Abstract: Carbon dioxide ion dissociations after inner shell excitation and ionization: The origin of sitespecific effects. Physics, 140(18) Multi-coincidence experiments with detection of both electrons and ions from decay of core-excited and core-ionized states of CO 2 confirm that O 2 + is formed specifically in Auger decay from the C1s-π * and O1s-π * resonances. Molecular rearrangement occurs by bending in the resonant states, and O 2 + is produced by both single and double Auger decay. It is suggested that electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…A theme throughout previous studies of bond rearrangement [8,11,14,22,23,[26][27][28][39][40][41][42] has been that the primary initiating step is the stimulation of bending modes in the triatomic molecule. With this background, it is not surprising that the bent water molecule has the highest bond rearrangement branching ratio of the molecules examined in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A theme throughout previous studies of bond rearrangement [8,11,14,22,23,[26][27][28][39][40][41][42] has been that the primary initiating step is the stimulation of bending modes in the triatomic molecule. With this background, it is not surprising that the bent water molecule has the highest bond rearrangement branching ratio of the molecules examined in this study.…”
Section: Resultsmentioning
confidence: 99%
“…as well as various photoionization studies[40, 41, 69-74, 87, 88].Several of these studies have noted the production of O + 2 fragments[26,27,40,41], although we are not aware of any reports of the branching ratio. The results of our double ionization branching ratio measurement for CO 2 are reported in TableIII.Two recent strong-field studies of CO 2 report the observation of the CO 2 + nω → O + 2 + C + process induced with laser pulses centered near 800 nm[26,27].…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The minor channel producing the SO + + C + ion pair was reported by Wang and Vidal 19 in 2003 using electron impact ionization, and was observed again in 2019 by Zhao et al 31 using strong field ionization. This ion pair can be formed only after bond rearrangement or by extreme bending of the molecules, as happens in CO 2 yielding O 2 + by Auger decay at the main long-lived π* pre-edge resonances 47–49 or after intramolecular isomerization upon double ionization as evidenced for SO 2 producing an O 2 + + S + pair. 50 Interestingly, Zhao et al observed that under strong field ionization conditions the angular distributions of CO + + S + and SO + + C + share the same behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the potential barrier of the CO + + O + channel is 1.00 eV. Meanwhile, for the isomerization channel C + + , Eland et al indicated that the minimum internal energy of 40.80 eV is required. Combining our calculation of the vertical ionization energy of , the potential energy barrier of the C + + channel is about 1.96 eV.…”
mentioning
confidence: 99%